THE PORTION OF THE RATIO THAT AFFECTS PROFITABILITY - Indrianasari, Neny Tri; Ifa, Khoirul; Lukiana, Ninik (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2021)
IC is considered a strategic aspect that is able to lead the company to gain and maintain a sustainable competitive advantage, therefore the measurement of intellectual capital performance allows the company to monitor which parts need to be improved in the IC aspect, with the aim of the company being able to generate greater profits in the future. This study aims to determine the effect of Intellectual Capital, Profit Sharing Ratio, Zakat Performance Ratio and Equitable Distribution Ratio on Profitability at BPR Syariah East Java Province. The type of research used in this research is descriptive research with a quantitative approach. The population used in this study were all Sharia Rural Banks (BPRS) of East Java Province which were recorded in the Financial Services Authority (OJK) for the selected period 2015-2018 with a population of 26 banks. The sample in this study was 15 banks which were selected by purposive sampling. This study concludes that the ratio of Profit Sharing Ratio and Equitable Distribution Ratio has no effect on profitability. Except Intellectual Capital and Zakat Performance Ratio have a significant effect on ROE.